Scientific genesis of operational and search measures to combat intentional homicide by the criminal police - Хижняк, Євген Сергійович; Хижняк, Є. С.; Хижняк, Евгений Сергеевич; Khyzhniak, Yevhen S.; Расюк, Едуард Вікторович; Расюк, Е. В.; Расюк, Эдуард Викторович; Rasiuk, Eduard V.; Чабанюк, Вадим Дмитрович; Чабанюк, В. Д.; Чабанюк, Вадим Дмитриевич; Chabaniuk, Vadym D.; et al. (Editorial Primmate S. A. S., 2021)
The aim of the article is to consider the scientific genesis of the problem of operational and investigative measures to combat intentional homicide by criminal police units. Subject of research is the stages on development of scientific knowledge on the issue under investigation. Methodology: In the course of the research the following methods are used: analysis and synthesis method, dialectical method, logical and semantic method, historical and legal method, legal modeling method. Research results: The state of scientific researches on the problem of crime prevention by the criminal police in general and intentional homicide in particular was examined. Practical consequences: In the course of the research, the development of scientific knowledge on the prevention of intentional homicide by criminal police units was gradually considered. Value / originality: It is the first study dedicated to the development of the history of prevention of intentional homicide by criminal police units in Ukraine.

Метою статті є дослідження наукового генезису проблеми оперативно –розшукової профілактики боротьби з умисними вбивствами підрозділами кримінальної поліції. Предметом дослідження є етапи розвитку наукового знання з проблематики, що досліджується. Методологія: У рамках статті були використані такі методи наукового знання: метод аналізу та синтезу, діалектичний метод, логічний та семантичний метод, історико-правовий метод, метод правового моделювання. Результати досліджень: Розглянуто стан наукових досліджень проблеми запобігання злочинності кримінальною поліцією в цілому та умисних вбивств зокрема. Практичні наслідки: У ході проведення дослідження поетапно було розглянуто розвитк наукового знання щодо запобігання умисним вбивствам підрозділами кримінальної поліції. Цінність / оригінальність: Це перше дослідження, присвячене розвитку інституту запобігання умисним вбивствам підрозділами кримінальної поліції в Україні.
Khyzhniak Y. Scientific genesis of operational and search measures to combat intentional homicide by the criminal police / Y. Khyzhniak, E. Rasiuk, V. Chabaniuk, Y. Myshkov, V. Davydiuk // Amazonia Investiga. - Vol. 10. - № 43. – Editorial Primmate S. A. S., 2021. – P. 200-208.
Keywords: scientific genesis; intentional homicide; prevention; criminal police units; historical development; науковий генезис; умисне вбивство; профілактика; підрозділи кримінальної міліції; історичний розвиток; Research Subject Categories::LAW/JURISPRUDENCE